Limits of usage of cost-benefit analysis by evaluation of public projects - Sobotková, Lucie (Univerzita Pardubice, 2014)
The article deals with the issue of evaluation of public projects which is based on the method of Cost-benefit analysis. The future social benefits and costs of public projects (financed especially from funds of the European Union) are evaluated by means of this method. We can practically meet the approach of set of social benefits and costs which arise from the assessment of present relevant economies. These economies are consequently predicted on the whole time of life cycle of the project. At the same time we simplify when we assign the present benefits to the particular years of lifetime of the project (we only respect the discount rate). This article proposes to involve the approach of system dynamics in the prediction. The system dynamics searches the reality as the system when the particular items of system are mutual influenced. The feed backs are raised when the result of the activity influences the original cause by return. The integration of the system dynamics into the evaluation of social benefits and costs could improve the prediction. Because the efficiency allocation of public resources is the aim of evaluation of public projects, the usage of system dynamics could support the process of allocation.
Keywords: cost-benefit analysis; methods of evaluation; public projects; simulation; system dynamics